2007
DOI: 10.1074/jbc.m609423200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mutational Analyses of the Major Cytosolic Exopolyphosphatase from Saccharomyces cerevisiae

Abstract: Yeast exopolyphosphatase (scPPX) processively splits off the terminal phosphate group from linear polyphosphates longer than pyrophosphate. scPPX belongs to the DHH phosphoesterase superfamily and is evolutionarily close to the well characterized family II pyrophosphatase (PPase -bound enzyme. These results provide an initial step toward understanding the dynamics of scPPX catalysis and reveal significant functional differences between structurally similar scPPX and family II PPase. Linear inorganic polyphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…the product pApA). The crystal structures of several DHH domain proteins revealed that the C-terminal subdomain (DHHA1 or DHHA2) is largely responsible for the binding of substrate (10,24,44). Sequence alignment of YybT and DHH family proteins revealed that although the DHH subdomain is fairly conserved with all the putative metal ion-binding residues ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…the product pApA). The crystal structures of several DHH domain proteins revealed that the C-terminal subdomain (DHHA1 or DHHA2) is largely responsible for the binding of substrate (10,24,44). Sequence alignment of YybT and DHH family proteins revealed that although the DHH subdomain is fairly conserved with all the putative metal ion-binding residues ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus sequence for the DHHA2 domain is often found in tandem with the DHH domain, but its function is unknown. With the exception of the well characterized exopolyphosphatases from S. cerevisiae (47,51) and L. major (19), there has been no biochemical examination of the members of the subfamily 2 of the DHH domain superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…The total concentrations of MgCl 2 and P 3 required to maintain the desired levels of free Mg 2+ ion and MgP 3 complex at pH 7.2 were calculated using the dissociation constants K 1 ) 3.63 µM and K 2 ) 1.91 mM for the MgP 3 and Mg 2 P 3 complexes, respectively (15). To convert the Michaelis constant obtained in terms of MgP 3 concentration into that in terms of total P 3 concentration, the former constant was divided by (1 (15), whereby k 1A and k 1B are second-order rate constants for MgP 3 binding, K M and K A are the dissociation constants for metal binding and k cat is the catalytic constant. Due to the high processivity of PPX, the substrate-binding step is assumed to be essentially irreversible.…”
Section: Methodsmentioning
confidence: 99%